(untitled) (Fiep Bulletin - online, 2014)
The study understood the determination of outstanding morphological, functional and technical characters that you/they enter the voleibolistas of category smaller than Metropolitan Lima, at federative and school level, with the purpose of determining a sport profile to offer a methodology of sport selection in the volleyball feminine Peruvian.The descriptive investigation, embraced the category minor, initiation stage and sport tendency. Prediminó the observation method through the use of technical of measurement and test instruments, control cards; the sample embraced voleibolistas that participate in national selection, clubs, selections of departments and of schools of Metropolitan Lima, with an approximate sample of 130 fellows. For the statistic treatment they were used: I average, standard deviation, variance rate and level of significance (t student); you program on-line of Heath Crankcase and Pedro Alexander for the determination of the morphological profile, somatotipo and corporal typesetting; for the level of physical performance you elaborarón scales and in the level technical control cardsThe obtained results determined: The somatotipo of National selection is ENDOECTOMORFO (2,5-2-4), those of Upper League and Distrital Ties MESOENDOMORFO (4,5-2-2 - and 4-4-2) respectively; the members of the Program Poles of Development enter a somatotipo ECTOENDOMORFO (10 years) with predominance of the ENDOMESOMORFO (11-14 years) and those of Educational Centers ENDOMESOMORFO.In the age bony, great percentage of the school sample he/she is with a premature increment (1,5 years) with relationship to the chronological age; the size average is bigger in subject of National Selection (175 cm), 3,8%, below the main selections of South America, the pettiest size corresponds to the school sample (155 cm); those subject of better sport performance enter a Diameter Biacromial half Relative and narrow pelvis (shoulders means and narrow pelvis), as well as an index Cormico: braquicómicoThe level of Physical Performance, is bigger in the members of National Selection with relationship to the league samples: saltabilidad (13,2%), it Forces Abdominal (44,4%), the Dorsal flexibility is 13,3%, the dinamometría it is bigger in the right hand as average is of 30,3 hand right, with a standard deviation of 8,97. The best technical level enters it the voleibolistas of more performance, case of national selection and Upper League (in 65%-70% of effectiveness), largely to its biggest makeready time